Photocatalyzed reductive fluoroalkylation of 2-acetoxyglycals towards the stereoselective synthesis of α-1-fluoroalkyl-: C -glycosyl derivatives - Mora Flores, Erwin Wilfredo (2020)
A benign, efficient, regio- and stereoselective protocol for the syntheses of α-1-fluoroalkyl-C-glycosyl compounds bearing CF3, C4F9, and C6F13 substituents on the anomeric carbon has been developed by a new methodology starting from 2-acetoxyglycals for the first time. Remarkably, the reactions proceeded in only one step, through the visible light-photocatalyzed reductive fluoroalkylation of 2-acetoxyglycals by means of an Ir photocatalyst and employed commercially available fluoroalkyl iodides n-CnF2n+1-I (n = 1, 4, 6) as a source of fluoroalkyl radicals.